Primary Spontaneous Brainstem Hemorrhage Leading to Sudden Cardiopulmonary Death: A Case Report - Inonu, Vanessa Faradise (Acta Neurologica Indonesia, 2025)
Introduction : Brainstem hemorrhage refers to bleeding that occurs in the pons, pontomedullary junction, pontomesencephalic junction, midbrain, and medulla oblongata. It is an uncommon form of intracerebral hemorrhage, with a prevalence of 5-10% in Indonesia, but it is associated with high mortality due to its critical location affecting vital functions. Case Report : A 57-year-old man, without significant personal or family medical history, presented at a private hospital with a severe headache. Initially, he was conscious, with normal blood pressure and a suspected diagnosis of stroke with 12th cranial nerve paresis. Within hours, his condition deteriorated rapidly, progressing to unconsciousness, coma, and cardiopulmonary death within four hours of admission. Computed tomography revealed a brainstem hemorrhage. Discussion : Primary Spontaneous Brainstem Hemorrhage (PBSH) is a rare but fatal form of stroke, often associated with hypertension, age, and personal living habits. However, in this case, no significant risk factors were identified except for age. The rapid deterioration from full consciousness to death highlights the aggressive nature of PBSH. Factors such as low Glasgow Coma Scale (GCS), tachycardia, hypotension, and the need for mechanical ventilation significantly contribute to poor outcomes. Brainstem hemorrhage leads to respiratory and vasomotor dysfunction, which can cause sudden death. Prompt management of respiratory and circulatory functions is crucial to improve survival chances. Conclusion : PBSH has a low incidence but high mortality, often leading to sudden death. Early detection and aggressive management of respiratory and circulatory complications are essential in preventing fatal outcomes.